Continuing professional education of highly-qualified personnel - (:unkn) unknown (My University, 1995)
"This report presents an analysis of the situation of continuing professional education of highly-qualified personnel in the various Member countries. While making no claims to compare, it does reveal the features specific to each country, and places them within more generall models of continuing education and higher education. Institutions of higher education are increasingly involved in orgoing professional education. Businesses, professional associations and the commercial sector are also quite present in this market. Together, and each with its specific contribution, these players help structure a training market and improved worker qualifications. This report analyzes how these changes, in seventeen OECD countries, are reshaping higher education and rasing challenges for policy-makers. It calls for a constructive dialoque enabling the various players in the sector to forge a coherent system for the very probable high growth in this sector. (author-s abstract, IAB- Doku) en; Der Bericht enthält die Ergebnisse einer Situationsanalyse der beruflichen Weiterbildung hochqualifizierter Arbeitskräfte in 17 Mitgliedsländern der OECD. (IAB2)
Keywords: G 1.3.1 Bildungsangebot & -nachfrage; S 2.3 Berufsbildungspolitik; G 1.2.3.2 Anforderungen & Bedarfe; Hochqualifizierter; Berufliche Weiterbildung; Bildungsangebot; Bildungspolitik; Bildungsbedarf; Quantitative Angaben; OECD; 1975-1989